Honesty as the Main Virtue: A Study of Al-Farabi's Moral Philosophy - Yuvita Nila Rahayu; Masniatul Ilmiah; Moch Imam Machfudi; Suparwoto Sapto Wahono (Penerbit Hellow Pustaka, 2025)
This study aims to analyze the concept of honesty within Al-Farabi’s moral philosophy through a library-based, conceptual, and philosophical approach. Honesty (shidq) is not merely understood as truthfulness in speech but as the harmony between knowledge, belief, and action grounded in human rationality and spirituality. The findings reveal that, in Al-Farabi’s ethical system, honesty represents a rational virtue linking theoretical and practical reason, serving as a moral principle that leads human beings toward ultimate happiness (sa‘ādah). Honesty also underpins social justice and political harmony, as elaborated in Al-Farabi’s notion of al-madīnah al-fāḍilah (the virtuous city). In the contemporary context, Al-Farabi’s conception of honesty remains highly relevant for character education, academic integrity, and public ethics in the digital age. Through the lens of Islamic moral philosophy, this study concludes that honesty is not only a moral virtue but also an ontological and epistemological principle that preserves the balance between truth, justice, and human happiness.